READING THE GENDERED NARRATIVES OF THE PANDEMIC THROUGH NAMITA GOKHALE’S “THE BLIND MATRIARCH” - Nupur, Das; Singh, Swati (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the intricate dynamics of power, gender, introspection, and identity within Namita Gokhale’s novel The Blind Matriarch. Through a detailed examination of the protagonist, Matangi-Ma, and other key characters, this study delves into how the pandemic exacerbates existing familial and societal tensions, leading to a profound exploration of themes such as isolation, alienation, belongingness, and identity crisis. The novel is set against the backdrop of the COVID-19 pandemic, which serves as a catalyst for the characters’ introspective journeys and the re-examination of their roles within the family and society. Matangi-Ma emerges as a central figure, embodying the strength and resilience required to navigate the complexities of these issues, while also highlighting the gendered power dynamics that shape the lives of the characters. Through a blend of narrative analysis and theoretical perspectives on gender and identity, this paper argues that The Blind Matriarch offers a compelling commentary on the intersections of personal and political power, the concept of home as a refuge and battleground, and the ongoing struggle for identity and belonging in a rapidly changing world.